p300/CBP is required for transcriptional induction by interleukin-4 and interacts with Stat6. - Gingras, S (1999)
Interleukin-4 (IL-4) induces tyrosine phosphorylation of the latent transcription factor Stat6, which mediates the transcriptional responses of IL-4. The transactivation domain of Stat6 has recently been mapped to the C-terminal region of Stat6. We have investigated the mechanism by which Stat6, through its transactivation domain, induces transcription. Previous studies have shown that diverse regulated transcription factors interact with coactivators such as p300 and CBP. We report that Stat6 used the interaction with p300/CBP to exert its stimulatory effects. Overexpression of p300/CBP increased IL-4-induced transcription of Stat6 activated reporter genes. The requirement of p300/CBP for Stat6-mediated transactivation is shown by coexpression of the adenovirus E1A protein. E1A repressed the IL-4-induced reporter gene activity, while mutants of E1A, which do not interact with p300/CBP, failed to block the IL-4-induced response. In addition, we found that the minimal transactivation domain of Stat6, when fused to the GAL4 DNA-binding domain, was repressed by E1A, whereas the fusion protein p300-VP16 increased the transcriptional activity. In two-hybrid protein interaction assays in mammalian cells, we mapped the interaction domain of CBP to a C-terminal region between amino acids 1850 and 2176, a region distinct from the interaction domain of CBP with Stat1, Stat2 or Stat5. Finally, we show that antibodies raised against p300 coimmunoprecipitated Stat6 and p300 from transfected COS7 cells and antibodies against Stat6 coimmunprecipitated endogenous Stat6 and CBP from Ba/F3 cells. Our data suggest that the transactivation domain of Stat6 makes contact with the basal transcription machinery by binding to p300/CBP.